Independent Associations of Circulating Galectin-3 Concentrations With Aortic Pulse Wave Velocity and Wave Reflection in a Community Sample. Issue 6 (June 2015) - Libhaber, Elena; Woodiwiss, Angela J.; Raymond, Andrew; Gomes, Monica; Maseko, Muzi J.; Sareli, Pinhas; Norton, Gavin R.
<x xml:space="preserve">Abstract</x> Although the profibrotic inflammatory substance galectin-3 predicts outcomes in the general population, the mechanisms responsible for this effect are uncertain. We aimed to determine whether circulating galectin-3 concentrations are associated with carotid femoral (aortic) pulse wave velocity and aortic reflective wave index (applanation tonometry and SphygmoCor software) in 966 randomly selected participants from a community sample. Galectin-3 concentrations were not independently associated with office (n=966) or 24-hour (n=661) systolic (P=0.88–0.92) or diastolic (P=0.65–0.94) blood pressure. In contrast, with adjustments for age, sex (in all participants), office or 24-hour mean arterial pressure (or systolic blood pressure and pulse pressure), pulse rate, body mass index, regular smoking, regular alcohol intake, total cholesterol concentrations, diabetes mellitus or an glycohemoglobin >6.1%, treatment for hypertension, and estimated glomerular filtration rate, galectin-3 was independently associated with aortic pulse wave velocity in all participants (partial r=0.15, P<0.0001) and reflective wave index in men (partial r=0.13, P<0.02). In 745 participants who had never received antihypertensive therapy, galectin-3 concentrations were similarly independently associated with pulse wave velocity in all participants (partial=0.16, P<0.0001) and reflective wave index in men (partial r=0.15, P<0.02). The blood pressure–independent relations between galectin-3 concentrations and aortic hemodynamics persisted with further adjustments for C-reactive protein concentrations (pulse wave velocity in all participants: partial r=0.14, P<0.0001; reflective wave index in men: partial r=0.12, P<0.05). In conclusion, despite a lack of independent association with brachial blood pressure, the profibrotic inflammatory substance galectin-3 may contribute toward adverse outcomes through an effect on aortic stiffness, an effect that cannot be attributed to general inflammatory changes.